REVIEW ON BIOLOGICAL WARFARE - ELIZABETH A.A.; MENEZES G.A. (International Journal of Pharma and Bio Sciences, 2013)
Biological warfare comprise of any intentional means to spread disease to humans, animals or plants. It includes a complex cluster of potentially deadly pathogens, genetically-engineered strain of highly infectious disease and toxins which can be delivered by variety of methods. Biological agents are easy to develop, more toxic than chemical weapons, less expensive and more difficult to detect than nuclear weapons. Disease or epidemics caused by biowarfare agents are not only a public problem but also breach of nation’s safety. In 2001 there were deadly anthrax attacks in the U.S mail and also the documents seized from Afghanistan by U.S. military force showing Al Qaeda’s interest in biological warfare in 2002, have served to enhance the concern about bioterrorism. It is vital to develop information and recognition of the dangers without unnecessarily boosting public anxiety and fear. This review tries to summarize the history and advances in biological warfare.